LEGALISASI SURAT KUASA OLEH KBRI (ANALISIS PUTUSAN KASASI NOMOR 659 K/AG/2010 TERHADAP SURAT KUASA KHUSUS BAGI WNI DI LUAR NEGERI) - Abdullah Ahmad Mukhtarzain; Fetri Fatorina; Chamid Sutikno (Economics, Social, and Humanities Journal (Esochum), 2023)
A special power of attorney made abroad has the same basic requirements as a power of attorney made domestically. The additional requirement for a special power of attorney made abroad is that there must be legalization from the Indonesian Embassy or local CONSULTATOR. The enactment of this regulation became the pretext for the defendant in the divorce case to appeal to the Semarang PTA against the Islamic civil case registration number 1304/Pdt.G/2009/PA-PWT. The defendant doubted the validity of the plaintiff's special power of attorney because there was no stamp or legalized stamp from the Indonesian Embassy (KBRI). The approach used is juridical-normative. The method used is data content-analysis and inductive-deductive. The findings of the Legalized research from the Embassy of the Republic of Indonesia (KBRI) or the Consulate General for Foreign Affairs are not a determinant of whether a special power of attorney is valid or not. Whether or not a special power of attorney is valid for Indonesian citizens who are abroad is determined by the fulfillment of the provisions of a special power of attorney in general as stated in SEMA Number 1 of 1971 in conjunction with SEMA Letter Number 6 of 1994 and the fulfillment of the provisions of an agreement contained in Article 1338 paragraph 1 Civil Code, Article 1320 Civil Code.